The Impact of a Construction Play on 5- to 6-Year-Old Children’s Reasoning About Stability - Weber, Anke Maria; Reuter, Timo; Leuchter, Miriam (Frontiers in Psychology, 2020)
Theory. Young children have an understanding of basic science concepts such as stability, yet their theoretical assumptions are often not concerned with stability. The literature on theory theory and theory-evidence coordination suggests that children construct intuitive theories about their environment that can be adjusted in the face of counterevidence that cannot be assimilated into the prior theory. With increasing age, children acquire a Center theory when balancing objects and try to balance every object at their middle, succeeding with symmetrical objects. Later, they acquire the basic science concept of stability through learning that the weight distribution of an object is of importance. Thus, they acquire a Mass theory and succeed in balancing asymmetrical objects as well. Fluid and crystallized intelligence might contribute to children’s acquisition of Mass theory. Moreover, their Mass theory might be supported by implementing a playful intervention including (a) material scaffolds and (b) verbal scaffolds. Aims. We investigated which theories children have about stability and whether these theories can be adjusted to Mass theory by implementing a playful intervention. Method. A total of 183 5- to 6-year-old children took part in the study with a pre-post-follow-up intervention design. Children’s Mass theory was assessed with an interview in which children explained constructions’ stabilities. The children received a playful intervention with two differing degrees of scaffolding (material scaffolds or material + verbal scaffolds) or no scaffolding. Results. At first few children used a Mass theory to explain their reasoning. However, after being confronted with counterevidence for the asymmetrical constructions, children changed their explanation and applied a Mass theory. More children in the play group with the highest degree of scaffolding, i.e., material + verbal scaffolds, acquired a Mass theory compared to the other groups. Fluid as well as crystallized intelligence contributed to children’s acquisition of a Mass theory. Discussion. Counterevidence can support children in their acquisition of a Mass theory. A playful intervention with scaffolding supports children even more.